THE IMPACT OF USER-GENERATED CONTENT (UGC) ON CUSTOMER ENGAGEMENT AND BRAND LOYALTY - Fadilah Kemala; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
The COVID-19 pandemic has made social media the latest information channel, encouraging firms to use it as a marketing channel. Creating relevant firm-generated content for consumers and social media users is one strategy that can be applied. This study is based on the service-dominant logic theory which aims to develop a conceptual framework involving variables of firm-generated content, customer engagement, user-generated content, consumer-based brand equity, and purchase intention. This study has 248 sample data and was analyzed quantitatively using the Structural Equation Modelling (SEM) method through the Analysis of Moment Structure (AMOS) version 24 program. The findings of this study show that customer engagement and consumer-based brand engagement as mediating variables have strengthened the relationship between firm-generated content and purchase intention. Specifically, there are significant effects for firm-generated content and user-generated content on customer engagement, user-generated content and customer engagement on consumer-based brand equity, and customer engagement and consumer-based brand equity on purchase intention. However, the relationship between customer engagement and purchase intention has proven no significant positive effect, so there is one rejected hypothesis.